Challenges in learning phonetics and phonology for UiTM TESL students / Muhammad Akram Abu Zait - Abu Zait, Muhammad Akram (Faculty of Education, 2014)
The study was conducted to study the challenges in learning phonetics and phonology. It was intended to study the understanding, rationale, challenges and the solution in learning phonetics and phonology for UiTM TESL students. A total of 30 students from Semester 8 were chosen as participants. A survey research method was used in this research. For numerous reason, the results indicate that these students are having difficulty in learning phonetics and phonology especially for those who had not been exposed to this subject in prior studies.